PENGARUH KOMISARIS ASING, DIREKTUR ASING DAN KEPEMILIKAN ASING TERHADAP KINERJA INTELLECTUAL CAPITAL - Noel S. H. Pradono; Elizabeth H. Widowati (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2016)
AbstractThis research aims to determine the effect of foreign commissioners, foreign directors and foreign ownership on intellectual capital performance of manufacturing firms in Indonesia Stock Exchange during 2012-2015. The sample used in this research composed of 20 companies with a span of 4 years or as many as 80 observations. This study used multiple linear regressions as statistical tools. The results are the proportions of foreign directors have significant positive effect on the intellectual capital performance while the proportion of foreign commissioners and the proportion of foreign ownership are not proven to have a significant effect on the intellectual capital performance.Keywords: intellectual capital performance, foreign commissioner, foreign director, foreign ownership